Upaya DP3APPKB Kabupaten Karanganyar dalam Memberikan Edukasi Kepada Masyarakat Akan Resiko Pernikahan Dini - Ninik Nitasari; Dwi Astutik (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Marriage is defined as an inner innate bond between a man and a woman to form a family that is sakinah, mawaddah, warahmah. Ideally, marriage is carried out by those who are mentally ready and old, but it is not uncommon to find many marriages under the age set by law. The marriage age limit is regulated in Law Number 16 of 2019 concerning Marriage, namely both men and women must be at least 19 years old. Data from UNICEF states that Indonesia alone has 1.2 million cases of underage marriage. The purpose of this study itself is to see the efforts made by the government in terms of overcoming the problem of early marriage in the Karanganyar area. The research method carried out is qualitative with a case study approach, or data is taken according to the stipulation of criteria that have been set previously. The results of the research obtained from the Karanganyar Regency DP3APPKB are efforts made by the government, namely by educating the public about the risks of early marriage and what negative impacts will be felt. The data is then processed using the structural perspective of Talcott Parsons' functionalism, in the concept of AGIL (Adaptation, Goal Attainment, Integration, Latency).